Increased expression of metadherin protein predicts worse disease‐free and overall survival in laryngeal squamous cell carcinoma. Issue 3 (7th March 2013) - Liu, Yong; Su, Zhongwu; Li, Guo; Yu, Changyun; Ren, Shuling; Huang, Donghai; Fan, Songqing; Tian, Yongquan; Zhang, Xin; Qiu, Yuanzheng
<x xml:space="preserve">Abstract</x> Metadherin (MTDH) is involved in tumourigenesis and cancer progression in multiple human malignancies. However, the MTDH protein has rarely been reported in laryngeal squamous cell carcinoma (LSCC). The expression pattern of the MTDH protein in 176 primary archival LSCC and 27 corresponding adjacent noncarcinoma specimens was detected by immunohistochemistry and further correlated with clinicopathological parameters. The results demonstrated that 161 (91.48%) primary LSCC samples stained positive for MTDH; however, staining was barely detectable in all adjacent noncarcinoma samples. Moreover, the expression of the MTDH protein was significantly associated with the primary tumour site (p = 0.021), T classification (p = 0.002), clinical stage (I + II/III + IV; p < 0.001), lymph node metastasis (p < 0.001) and postoperational recurrence (p < 0.001). Kaplan‐Meier analysis revealed that MTDH expression was significantly associated with worse disease‐free survival (DFS) and overall survival (OS) rates in patients with LSCC (both p < 0.001). When lymph node metastasis and MTDH expression were considered together, patients with lymph node metastasis and high MTDH expression had both poorer DFS and OS rates than others (both p < 0.001). Finally, multivariate analysis demonstrated that MTDH expression was an independent prognostic factor for both DFS and OS rates in patients with LSCC. Strong MTDH expression was negatively correlated with a canonical epithelial–mesenchymal transition molecule E‐cadherin (p < 0.001) and positively associated with proangiogenic protein vascular endothelial growth factor (p < 0.001). MTDH overexpression was tightly associated with more aggressive tumour behaviour and a poor prognosis, indicating that MTDH is a valuable molecular biomarker for LSCC progression.